The Life and Music of Oliver Mtukudzi
XIV, 295 p.
Keywords: This book is a critical reflection on the life and career of the late legendary Zimbabwean music icon, Oliver “Tuku” Mtukudzi, and his contribution towards the reconstruction of Zimbabwe, Africa and the globe at large. Mtukudzi was a musician, philosopher, and human rights activist who espoused the agenda of reconstruction in order to bring about a better world, proposing personal, cultural, political, religious and global reconstruction. With twenty original chapters, this vibrant volume examines various themes and dimensions of Mtukudzi’s distinguished life and career, notably, how his music has been a powerful vehicle for societal reconstruction and cultural rejuvenation, specifically speaking to issues of culture, human rights, governance, peacebuilding, religion and identity, humanism, gender and politics, among others. The contributors explore the art of performance in Mtukudzi’s music and acting career, and how this facilitated his reconstruction agenda, offering freshand compelling perspectives into the role of performing artists and cultural workers such as Mtukudzi in presenting models for reconstructing the world. Ezra Chitando (PhD) is Professor of Religion in the Department of Philosophy, Religion and Ethics at the University of Zimbabwe, and Theology Consultant on HIV and AIDS for the World Council of Churches. He researches and publishes on music, religion and culture. He is the author of Sounds of Life: Music, Identity and Politics in Zimbabwe, (2016, co-edited with Mangena and Muwati), along with numerous other publications. Pauline Mateveke (PhD) is a Senior Lecturer in the Department of Language, Literature and Culture at the University of Zimbabwe. She holds a Doctor of Philosophy Degree in English specialising in Gender, Literature and Music. Her research interests include popular culture and literature, gender studies and literary criticism. Munyaradzi Nyakudya (PhD) is a Senior Lecturer in the Department of History, Heritage and Knowledge Systems at the University of Zimbabwe. He researches on the socio-political and economic history of African societies, with a special passion for ethnomusicology, peace and security studies; education, democratization and sustainable livelihoods. Bridget Chinouriri (PhD) is a Zimbabwean ethnomusicologist, creative writer, culture consultant and scientist and a Senior Lecturer in the Department of Creative Media and Communications, University of Zimbabwe.